Edukasi Kesehatan Gigi dan Mulut serta Cara Menggosok Gigi pada Anak Sekolah Dasar di Banjar Bukian, Desa Pelaga - Komang Trisna Sumadewi; Saktivi Harkitasari (Warmadewa University Press, 2023)
Abstract One of the most prevalent oral and dental conditions in children aged 7 to 12 is dental caries. In Indonesia, oral and dental health are not yet given high emphasis, and if complaints do not get in the way of daily activities, people are inclined to disregard them. A person's social life, quality of life, and sense of self-worth can all be impacted by having a clean, healthy mouth, which can also have an impact on school-age children's growth and development. It is crucial to adopt a clean and healthy lifestyle early on because the school-age years are a crucial time for shaping children's habits that will last into adulthood. Correct tooth brushing is a part of living a clean and healthy lifestyle. Teaching kids how to properly brush their teeth can lower their risk of developing cavities or dental caries. This community service project aims to improve the ability of parents and elementary school students to correctly brush their teeth as well as their awareness and comprehension of dental and oral health. Based on these issues, a program was implemented that included teaching kids about dental and oral health, showing them how to clean their teeth properly, and helping them brush their teeth. It is believed that this training will help with the issues raised and improve knowledge and abilities for brushing teeth effectively. At Bukian Banjar, Pelaga Village, the program for teaching dental and oral health awareness and the appropriate way to clean your teeth went off without a hitch, with every participant in attendance. The pretest and posttest findings show that the participants' knowledge increased by 100%. Based on the findings of mentoring observations, it was discovered that elementary school students had improved tooth-brushing abilities. Such actions ought to be taken on a regular basis with broader objectives in order to lower the frequency of dental caries and enhance each person's quality of life.